Not Whether, But When? Governments' Use of Militias in War. (20th October 2019) - Ambrozik, Caitlin
Abstract: Although government use of militias during civil conflict can ultimately undermine state authority, governments still use militias for battlefield assistance. This paper examines the selectivity of government decisions to use militias by disaggregating civil conflict to the level of battle phases. Civil-conflict battles typically consist of four phases: preparation, clear, hold, and build. I argue that governments decide to use militias based on the strength of government security forces, operational advantages of militias, and the type of battle phase. Governments will limit the use of militias during key battle phases that are likely to receive increased media attention unless a victory secured by government security forces is unlikely or militias hold an operational advantage. A comparative analysis of the offensive operations in Tikrit and Ramadi during Iraq's war against the Islamic State of Iraq and Syria (ISIS) lends initial support to this theory.